Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1203475415604551
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Autoimmune Thyroid Disease in Patients With Progressive and Stable Vitiligo

Abstract: This study not only confirmed thyroid dysfunction in patients with vitiligo but also showed that there was no difference in thyroid dysfunction and anti-TPO antibody levels in the subgroups of patients with stable or progressive vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 9 publications
2
11
0
1
Order By: Relevance
“…This finding suggests that the risk of AITD increases with age. Similar results were obtained by another study that found thyroid disorders to be more common in patients over 30 years of age . Contrary to this, Bae et al .…”
Section: Specific Autoimmune Comorbiditiessupporting
confidence: 87%
See 4 more Smart Citations
“…This finding suggests that the risk of AITD increases with age. Similar results were obtained by another study that found thyroid disorders to be more common in patients over 30 years of age . Contrary to this, Bae et al .…”
Section: Specific Autoimmune Comorbiditiessupporting
confidence: 87%
“…This finding suggests that the risk of AITD increases with age. Similar results were obtained by another study that found thyroid disorders to be more common in 39 Contrary to this, Bae et al 40 found the association between vitiligo and both Graves' disease and Hashimoto's thyroiditis to be strongest in children and adolescents.…”
Section: Thyroid Diseasesupporting
confidence: 79%
See 3 more Smart Citations